The interplay between market factors and regulation in next-generation broadband: evidence from Europe - Tricia Ragoobar; Jason Whalley; David Harle (International Telecommunications Society (ITS), 2010)
Although many factors affect next-generation access (NGA) deployment, regulatory frameworks have the power to guide future investments, further development and, consequently, the competitiveness of a next-generation broadband market. Understanding the link between markets and regulatory requirements, therefore, is essential. Using data collected from broadband stakeholders in three markets, this paper provides an empirical analysis of this relationship. The market conditions in The Netherlands, Sweden and the United Kingdom (UK) and their roles in influencing the regulatory decisions made by the respective national regulatory authorities (NRAs) are examined. Such analysis first shows that market conditions present different priorities for regulators and policymakers. While markets with weaker incentives for investment, such as the UK, are in need of regulatory and public policy intervention, The Netherlands and Sweden require less stringent measures. Despite this, evidence shows that some level of NGA regulation is presently required in all three markets, albeit to varying degrees and with different foci. The paper then highlights the interaction of the market factors, explaining that this interrelationship is more important for policymakers than the effects of a single factor. The findings of the paper are useful for regulators in addressing the challenges of next-generation broadband deployment.
Keywords: 330; Next-generation access; Regulation; The Netherlands; Sweden; United Kingdom; Comparison